(untitled) (Prithvi Journal of Research and Innovation, 2025)
This paper is to analyze the relationships between the green organizational culture (GOC) and employee performance (EP), and the impact of GOC on EP in higher education institutions (HEIs) in Pokhara Metropolitan City.The relationship has been analyzed from the perspective of non-teaching staff of HEIs. The study is based on objectivism ontology and used descriptive and causal comparative research design, using the quantitative survey approach. The study sampled 55 non-teaching staff from five HEIs that include both constituent and public campuses of the study area. The independent variables are clan, adhocracy, hierarchy and market culture that constitute GOC and the dependent variable includes EP that was constructed with task, contextual and adaptive performance. Adopting correlation and regression analysis, the study was found that the independent variables have an average positive significant relationship to the dependent variable. These are lower than the average impact on the dependent variable by the independent variables. There is a positive significant impact of only the market culture on EP. The practice of GOC is more or less alike the public and constituent campuses. Hence, the GOC is compulsory for enhancing the performance of non-teaching staff of HEIs. This paper has practical, theoretical and policy implications and also provide some insights for upcoming research to make various institutions green.